2022
DOI: 10.7575/aiac.ijkss.v.10n.3p.7
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Acute Exercise and Virtual Reality Tasks on Children’s Memory Function and Exercise Preference

Abstract: Background: It is well established that regular participation in exercise and virtual reality (VR) environments are important tools for improving or maintaining human health and cognitive function. Objectives: This study examined the effects of acute exercise and VR environments on children’s memory function and exercise preference (i.e. cycling with or without the use of VR technology). Methods: Α 2×3 factorial design was adopted with two measures (pre, post) and three study groups. Forty-five healthy childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Other research also confirmed that virtual reality physical activity had a positive effect on cognitive function in adults [39]. Krommidas et al [52], reported similar results, virtual reality-based physical activity had a higher score than the control group in developing cognitive function in children. In addition, according to Bauer & Andringa [65], virtual reality was an effective form of cognitive training for providing an immersive and interactive environment with real simulations which was suggested as a tool in improving cognitive function.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Other research also confirmed that virtual reality physical activity had a positive effect on cognitive function in adults [39]. Krommidas et al [52], reported similar results, virtual reality-based physical activity had a higher score than the control group in developing cognitive function in children. In addition, according to Bauer & Andringa [65], virtual reality was an effective form of cognitive training for providing an immersive and interactive environment with real simulations which was suggested as a tool in improving cognitive function.…”
Section: Discussionmentioning
confidence: 61%
“…Participants were recruited randomly, in the first stage the researchers sent invitation letters to athletes and got positive response from all athletes, in the second stage they were required to create and sign a letter of willingness to participate in this study. Researchers used G Power analysis to calculate the required sample size in this study and the result was a of 15 athletes in each group [52]. After fulfilled the sample size criteria, the athletes were allocated to the experimental group which received a virtual realitybased physical exercise program (n=15, mean±SD: age = 14.13±0.6 years, weight = 44.60±3.3 kg, height= 1.34±0.8 cm) and the control group (n=15, mean±SD: age= 13.80±0.8 years, weight= 43.60±2.7 kg, height= 1.32±0.9 cm).…”
Section: Methodsmentioning
confidence: 99%
“…According to the results of a study, that examined the effects of acute VR exercise combined with cognitive tasks on children's memory and exercise preference, children who experienced VR exercise noted higher scores in memory tests compared with children who experienced a traditional cycling session and control group. Additionally, children showed high levels of enjoyment, intention for future use, and attitudes toward cycling in a VR environment [28]. Acute VR exergaming can also lead to mood improvement according to Ochi et al (2022) [33].…”
Section: Ivr Systemmentioning
confidence: 98%
“…VR exercise combined with cognitive tasks, according to another study, appeared to be appropriate and had positive effects even in people with mild cognitive impairment [27]. Additionally, recent research by Krommidas et al (2022) [28] has highlighted the potential of acute exercise and virtual reality tasks to positively impact children's memory function and exercise preference, providing valuable insights into the broader applications of VR-based exercise interventions. VR environments are also a reliable way for providing information about addictive disorders, such as the desire to use, and can influence emotional state, attention, and cognitive function [29].…”
Section: Introductionmentioning
confidence: 95%
“…It is important to mention that all the above-mentioned instruments have already been translated into the Greek language and have been used previously in studies with a Greek population [31][32][33].…”
mentioning
confidence: 99%